Region-Specific Reductions in Morphometric Properties and Synaptic Colocalization of Astrocytes Following Cocaine Self-Administration and Extinction - Testen, Anze; Sepulveda-Orengo, Marian T.; Gaines, Christiann H.; Reissner, Kathryn J. (Frontiers in Cellular Neuroscience, 2018)
While much is known about the effects of cocaine use on the cellular structure and function of neurons and synapses within the brain’s reward circuitry, relatively little is known about the effects of cocaine on astrocytes. Given the significant role that astrocytes play in modulating neuronal and synaptic function, this lack of knowledge regarding the role of astroglial adaptations in the neuropathology of drug abuse represents an important investigative need. We recently showed that astrocytes within the nucleus accumbens (NAc) core exhibit decreased volume, surface area, and synaptic colocalization following cocaine self-administration and extinction, compared to NAc astrocytes from saline-administering animals (Scofield et al 2016b). However, it is unknown whether these cocaine-dependent changes in astrocytes are ubiquitous throughout the brain’s reward circuitry, or represent specific adaptations within the NAc. It is also not known whether the extinction period is necessary for the retracted phenotype, or whether self-administration alone is sufficient to drive these changes. In the current study, we have extended our assessment of the effects of cocaine self-administration on morphometric properties and synaptic colocalization of astrocyte peripheral processes in the prelimbic region of the medial prefrontal cortex (PL) and basolateral nucleus of the amygdala (BLA), both known to also contribute significantly to motivated behaviors. In addition, in order to pinpoint the temporal dimension of previously observed effects, we also examined astrocytes within the NAc following the last self-administration session. While a reduction of astrocyte size and synaptic colocalization was observed in the NAc core of cocaine-extinguished rats as previously shown, no differences in PL or BLA astrocytes were observed between saline- and cocaine-extinguished rats. Moreover, decreased synaptic colocalization of peripheral processes in the NAc was observed with a postsynaptic marker, instead of a presynaptic marker as used previously. In contrast, no significant changes were found in NAc astrocytes after self-administration alone. These results provide insights into the influence of cocaine use on astrocytes within the brain reward circuitry, and inform both regional heterogeneity as well as temporal dynamics of astrocyte responsiveness to cocaine self-administration.